Treatment of Plasmodium falciparum malaria with pyrimethamine-sulfadoxine: selective pressure for resistance is a function of long elimination half-life - Watkins, W M; Mosobo, M (Transactions of the Royal Society of Tropical Medicine and Hygiene, 1993)
In an area of continuing transmission of Plasmodium falciparum on the Kenya coast, children treated with pyrimethamine-sulfadoxine experienced rapid parasite clearance, although a high proportion became reinfected within a short time. The frequency of pyrimethamine resistance in vitro in new infections was higher during the elimination phase of drug from a previous treatment. In infections which occurred at times when predicted residual drug concentrations were no longer inhibitory, incidence of pyrimethamine resistance was no different from the natural or background frequency. These results are discussed in terms of the selective pressure for resistance which is exerted by drugs with long elimination half-lives and a consideration of possible ways by which the problem might be addressed.